Child Physical Activity Propensity and Parent Physical Activity Cognitions Behaviors and the Home Environment (P16-011-19). (13th June 2019) - Delaney, Colleen; Eck, Kaitlyn; Byrd-Bredbenner, Carol
Abstract: Objectives: To examine the relationship between child physical activity (PA) propensity (i.e., tendency to be physically active) and parent PA cognitions and behaviors, as well PA-related aspects of the home environment. Methods: Parents ( N = 390) of young children (ages 2–9) completed an online survey assessing their PA cognitions, behaviors, home environment, and children's PA-propensity. Parents with child PA-propensity scores below the median ( n = 141) were compared to those above with scores above the median ( n = 249) compared using t-test. Results: Parent PA cognitions differed significantly ( P < 0.01) by child PA-propensity. Using 5-point scales, parents with high PA-propensity children tended to place more value on PA for themselves (3.01 ± 1.13 SD vs. 2.70 ± 1.09 SD) and their children (3.90 ± 0.88 vs. 3.41 ± 0.84 SD) than parents with low PA-propensity children. Parents with high PA-propensity children were significantly more likely to encourage and facilitate children's PA (4.15 ± 0.68 SD vs. 3.80 ± 0.60 SD), engaged in PA with their children more frequently (4.06 ± 1.88 SD vs. 3.11 ± 1.69 SD), and had more self-efficacy for promoting child PA (3.64 ± 1.01 SD vs. 3.25 ± 1.06 SD) than comparators. Parents with high PA-propensity children also placed greater importance on modeling healthy PA behaviors to their children (3.97 ± 0.84 SD vs. 3.74 ± 0.82 SD) and modeled these behaviors more often (2.72 ± 1.74 SD vs. 2.07 ± 1.67 SD) than the comparison group. PA level, measured using 42-point scales indicated parents with high PA-propensity children had higher PA levels (14.94 ± 10.31 SD vs. 11.57 ± 9.00 SD) as did their children (28.35 ± 11.41 SD vs. 21.62 ± 11.40 SD) than parents with low PA-propensity children. Home environments assessments (5-point scales) revealed parents with high PA-propensity children reported more indoor/home (3.44 ± 0.83 SD vs. 3.20 ± 0.86 SD) and outdoor/yard (4.39 ± 0.64 SD vs. 4.13 ± 0.78 SD) space and supports for PA than the comparison group. Conclusions: Parents with higher child PA-propensity had more positive PA cognitions and behaviors, and had home environments more supportive of PA. Future research aiming to increase family PA levels should consider the potential effect parent perceptions of child PA-propensity and consider tailoring interventions based on these perceptions. Funding Sources: 2011-68001-30170 and 2017-680001-26351.